Bone status in adults with early-onset juvenile idiopathic arthritis following 1-year anti-TNFα therapy and discontinuation of glucocorticoids - Brabnikova Maresova, Kristyna; Jarosova, Katerina; Pavelka, Karel; Stepan, Jan J (Rheumatology international, 2013)
Juvenile idiopathic arthritis (JIA) is an inflammatory disease associated with bone loss and low bone mineral density (BMD). The treatment involves disease-modifying antirheumatic drugs, glucocorticoids (GCs) and biological agents. The aim of this study was to evaluate effects of 12-month therapy with the anti-tumor necrosis factor alpha (anti-TNFα) preparations on bone mineral density (BMD) and biochemical turnover markers (BTM) in adult patients with JIA who were previously either treated or not treated with glucocorticoids (GC) and to assess effects of the discontinuation of GCs on their bone status. Nineteen adult patients (12 women, 7 men) aged 18-33 years with active JIA were prospectively enrolled to receive the anti-TNFα therapy (infliximab, etanercept or adalimumab). BMD and BTMs were determined at baseline and 1-year follow-up. The anti-TNFα therapy resulted in a significant reduction in disease activity score 28 (DAS28) and C-reactive protein (CRP) and a significant increase in BMD at the lumbar spine and total body and in serum N-terminal propeptide of type I procollagen (PINP, marker of bone formation). No significant changes in serum beta C-terminal telopeptide of type I collagen (βCTX, marker of osteoclastic bone resorption) and osteocalcin (marker of bone remodeling) were found. A significant negative correlation was observed between the change in the DAS28, CRP and serum PINP. The change in serum PINP concentrations positively correlated with the change in lumbar spine BMD. A significant increase in serum PINP was observed only in patients discontinuing GCs during the anti-TNFα treatment. After the initiation of the anti-TNFα therapy in young adults with JIA, the increase in new bone formation can be explained by discontinuation of GCs administration as the patients with the largest reduction in DAS28 and CRP probably are the ones most likely to stop GC.
Keywords: dospělí; infliximab; Infliximab; kolagen typu I; etanercept; Procollagen; Female; radiografie; Etanercept; biologické markery; C-Reactive Protein; Radiography; imunoglobulin G; Biomarkers; Adult; výsledek terapie; ženské pohlaví; Tumor Necrosis Factor-alpha; kostní denzita; Adolescent; adalimumab; Bone Density; Antibodies, Monoclonal; kosti a kostní tkáň; lidé; osteokalcin; Osteocalcin; Treatment Outcome; remodelace kosti; Immunoglobulin G; TNF-alfa; Receptors, Tumor Necrosis Factor; Male; Antirheumatic Agents; Bone Remodeling; monoklonální protilátky; humanizované monoklonální protilátky; juvenilní artritida; C-reaktivní protein; receptory TNF; mužské pohlaví; Antibodies, Monoclonal, Humanized; Arthritis, Juvenile; antirevmatika; Collagen Type I; Bone and Bones; mladiství; Adalimumab; prokolagen; Humans